An Application of the Arba'in Method in Learning How to Quickly Read the Kitab Kuning at Ma'had Tahfizh Al-Izzah Zam-Zam Surakarta - Dudi Budi Astoko; Imam Suhadi; Farid Wahyudin (CV. Creative Tugu Pena, 2024)
This study aims to analyze the effectiveness of the Arba’in method in improving the reading and comprehension skills of students at Ma’had Tahfizh Al-Izzah Zam-Zam Surakarta regarding kitab kuning. The method employed is a qualitative approach using observations, interviews, and document analysis to gather data from students and teachers. The findings indicate that the Arba’in method is effective in simplifying students’ understanding of Arabic grammar rules, particularly in the field of nahwu. Through structured memorization and practical exercises, students can enhance their reading speed and comprehension of classical texts. Furthermore, the application of this method also boosts students' confidence in analyzing and discussing kitab kuning. This study concludes that the Arba’in method not only enhances students' technical abilities but is also relevant in the context of contemporary Islamic education. It is hoped that the findings of this research can serve as a reference for other educational institutions in implementing effective teaching methods to improve Arabic language proficiency and understanding of Islamic literature.